Estimates of intergenerational elasticities based on lifetime earnings - Øivind Anti Nilsen; Kjell Vaage; Arild Aakvik; Karl Jacobsen (Institute for the Study of Labor (IZA), 2008)
Using Norwegian intergenerational data with a substantial part of the life-cycle earnings of children and almost the entire life-cycle earnings for their fathers, we present new estimates of intergenerational mobility. Extending the length of the fathers' earnings windows from 5 to 30 years increases the estimated elasticities. Increasing the age of father at observation has the opposite effect. Our findings indicate that intergenerational earnings mobility may have been strongly overstated in many earlier studies with shorter earnings histories. Biases in the estimated elasticities appear to be related to age and/or life-cycle measurement errors more than persistency in the transitory innovations.
urn:nbn:de:101:1-2008101476
Keywords: J62; 330; Intergenerational mobility; measurement error; Soziale Mobilität; Generationenbeziehungen; Familiensoziologie; Lebenseinkommen; Norwegen